2015
DOI: 10.1016/j.jtemb.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an optimized method for the determination of iodine in human breast milk by inductively coupled plasma mass spectrometry (ICPMS) after tetramethylammonium hydroxide extraction

Abstract: In all cases accepted manuscripts should: link to the formal publication via its DOI  bear a CC-BY-NC-ND license -this is easy to do, click here to find out how  if aggregated with other manuscripts, for example in a repository or other site, be shared in alignment with our hosting policy  not be added to or enhanced in any way to appear more like, or to substitute for, the published journal article Embargo ISSN Journal Name Embargo Period (months) 0946-672X Journal of Trace Elements in Medicine and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…Studies reporting BMIC using the SandellKolthoff method without reporting information on external quality control should be interpreted cautiously. ICP-MS is the gold standard for determination of lowiodine concentrations in complex matrices (21,22,26,29,30) and the preferred method for BMIC. The data demonstrate the importance of the choice of ICP-MS quantification procedure for BMIC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies reporting BMIC using the SandellKolthoff method without reporting information on external quality control should be interpreted cautiously. ICP-MS is the gold standard for determination of lowiodine concentrations in complex matrices (21,22,26,29,30) and the preferred method for BMIC. The data demonstrate the importance of the choice of ICP-MS quantification procedure for BMIC.…”
Section: Discussionmentioning
confidence: 99%
“…One study found differences in BMIC between fore-and hind-milk samples (17) while another did not (18). Broad ranges of BMIC have been reported in iodine-sufficient countries (9)(10)(11)19), but comparing BMIC across studies is difficult because of differences in study design, analytical methods, and the lack of external quality control (9,17,(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
See 3 more Smart Citations